EFEKTIVITAS PENERAPAN BRIDGE TEAM MANAGEMENT (BTM) TERHADAP KESELAMATAN PELAYARAN DI SPV STAR CLIPPER - Meinaldo Hayatullah Marthind; Budiawan; Muhlisin (STKIP Subang, 2026)
This study aimed to analyze the effect of Bridge Team Management (BTM) implementation on navigation safety aboard SPV Star Clipper. The study was grounded in the importance of human factors in maritime safety, particularly in sailing passenger vessel operations that require bridge-deck coordination, sail handling, situational awareness, and clear communication among multinational crew members. This study employed a quantitative explanatory approach. Data were collected through Likert-scale questionnaires, observation, and documentation involving 30 Deck Officers and crew members selected using purposive sampling. Data analysis included validity, reliability, descriptive statistics, Shapiro-Wilk normality, linearity, heteroscedasticity, simple linear regression, t-test, and coefficient of determination using IBM SPSS Statistics 25.0. All questionnaire items were valid and reliable, with Cronbach's Alpha values of 0.986 for BTM and 0.983 for navigation safety. The regression analysis produced the equation Y = 3.724 + 0.945X. The t-count value of 33.686 exceeded the t-table value of 2.048, with Sig. = 0.000 < 0.05. The coefficient of determination (R2) of 0.976 indicated that BTM explained 97.6% of the variation in navigation safety. Therefore, BTM implementation has a positive and significant effect on navigation safety aboard SPV Star Clipper. Clear communication, coordination, leadership, situational awareness, and timely decision-making are essential elements in supporting safe ship operations.